The triazole fungicide metconazole inhibits the homodimerization of human androgen receptors to suppress androgen-induced transcriptional activation. (1st June 2023) - Jung, Da-Woon; Jeong, Da-Hyun; Kim, Uk-Jin; Lee, Hee-Seok
Abstract: We assessed the mechanism of human androgen receptor-mediated endocrine-disrupting effect by a triazole fungicide, metconazole in this study. The internationally validated stably transfected transactivation (STTA) in vitro assay, which was established for determination of a human androgen receptor (AR) agonist/antagonist by using 22Rv1/MMTV_GR-KO cell line, alongside an in vitro reporter-gene assay to confirm AR homodimerization was used. The STTA in vitro assay results showed that metconazole is a true AR antagonist. Furthermore, the results from the in vitro reporter-gene assay and western blotting showed that metconazole blocks the nuclear transfer of cytoplasmic AR proteins by suppressing the homodimerization of AR. These results suggest that metconazole can be considered to have an AR-mediated endocrine-disrupting effect. Additionally, the evidence from this study might help identify the endocrine-disrupting mechanism of triazole fungicides containing a phenyl ring. Graphical abstract: Image 1 Highlights: Metconazole has endocrine-disrupting effect. Metconazole was determined as an AR antagonist in transcriptional activation assay. Metconazole inhibited the dimerization of AR in cytoplasm. The 'dimerization' inhibition causes to block the nuclear translocation of cytoplasmic AR proteins. AR antagonistic effect is caused by inhibiting the dimerization of ligand-bound ARs in cytoplasm.